Elementary Steps in T Cell Receptor Triggering - Dushek, Omer (Frontiers in Immunology, 2012)
The mechanism by which antigen binding to the T cell antigen receptor (TCR) generates intracellular signaling, a process termed TCR triggering, is incompletely understood. A large body of experimental evidence has implicated multiple biophysical/biochemical effects and multiple molecules in the process of TCR triggering, which likely reflect the uniquely demanding role of the TCR in recognizing diverse antigenic ligands. In this perspective, I propose that breaking down the process of TCR triggering into tractable elementary steps may be a useful approach in building mechanistic TCR triggering models. Once these elementary steps are understood, they can be recombined to build a unified model of TCR triggering.